2020
DOI: 10.1088/1742-6596/1486/3/032038
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic vessel segmentation based on animproved 3D region growing algorithm

Abstract: Hepatic vessel segmentation of CT image is of great importance in the computer aided diagnosis. This paper proposes an automatic segmentation method of 3D vessel CT images to obtain better segmentation results. First, the single Gaussian kernel of Hessian matrix in the Jerman’s algorithm is replaced by bi-Gaussian kernel. Then, a histogram-based method is adopted to adaptively estimate the threshold value of the region growing. Finally, a new scheme is proposed forautomatically searching seed points of the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The traditional machine-learning techniques that are borrowed for vessel segmentation include active contour or level set [4], graph cut [5,6], extreme learning machine [7], vascular filters [8,9,10], and still many others [11,12,13,14]. These approaches can fish out vessels from CT images with moderate accuracy and timesaving.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional machine-learning techniques that are borrowed for vessel segmentation include active contour or level set [4], graph cut [5,6], extreme learning machine [7], vascular filters [8,9,10], and still many others [11,12,13,14]. These approaches can fish out vessels from CT images with moderate accuracy and timesaving.…”
Section: Introductionmentioning
confidence: 99%
“…The Couinaud representation of the liver is another important feature of clinicians' interest for locating tumors or surgical planning. The evolution of computer science in research on image segmentation has revealed interest in the reconstruction and interpretation of these complex organic structures [1,2]. Their robust extraction from biomedical images requires good acquisition during an imaging examination and advanced image analysis developments.…”
Section: Introductionmentioning
confidence: 99%